Characterization of fly ash and it effects on the compressive strength properties of Portland cement - Celik, Oezlem; Damei, Erdem; Piskin, Sabriye (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2008)
In this study, the structure of, different type of fly ash samples collected from different thermal power plants (Soma Unit IV/ type C Catalagzi/type F, Cayirhan / type C, Tuncbilek/ type F) in Turkey has been investigated. The chemical and physical properties, mineralogical composition and particle size distributions of the samples and their effects oil the compressive strength properties of ordinary Portland cement (OPC), have been determined by FTIR, XRD, Mastersizer and SEM. Characterization results show that either Soma Unit IV and Tuncbilek or Catalagzi and Cayirhan fly ash samples give similar structure of peaks in FTIR/ATR separately. Particle size distribution and SEM results also Support each other. There are overlaps between characterization results of fly ash samples and compressive strength,results of fly ash mortars. The cement mortars are prepared and tested for compressive strength according to the European Standards (EN 196-1). Results indicate that fly ash samples in the ratio of 15% in clinker markedly increases the compressive strength value (61.1 N/mm(2)) at 90 days. It indicates that decreasing the particle size of fly ash in blended Portland cement causes an increase in compressive strength. This means that fineness is a more effective parameter than chemical composition in improving the strength development of fly ash mortars and it is suggested that fine fly ash call be used to obtain higher compressive strength values.
Keywords: Portland cement; Fly ash; XRD; SEM; FTIR/ATR; Mastersizer; PARTICLE-SIZE; MICROSTRUCTURE; CONCRETE; Engineering; Materials Science